Memaknai Penderitaan Orang Hidup dalam Kristus dalam Kitab Ayub - Evi Mariani; Robert Betaubun (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
The background of this paper is to present thinking as an activity for interpreting the story of Job through a life in constant suffering. Thinking about suffering is not a new idea in theological circles, but it has always existed, and even suffering is considered an inseparable part of happiness. For this reason, suffering, which is often reflected in cross-cutting ways, becomes a problem when looking at different perspectives of theology, especially those that talk about suffering and hope in the case of Job's life. The story of Job offers insight that suffering is not always synonymous with punishment, but can be a test of faith or a means of spiritual growth. This message is very relevant in the modern era, especially in the face of a crisis situation such as the pandemic, where Christians are reminded to see suffering as part of the divine plan. From an academic perspective, an analysis of Job's suffering expands the discussion on the theology of retribution, by showing the relationship between God and humans as more dynamic than transactional. This understanding can encourage a more mature response of faith in facing life's challenges. The purpose of this study is to find the meaning of humanity and faith, theological retribution, and the mystery of God for human beings in the history of wisdom literature in the Books of Job and the Psalms. This research method is qualitative research with literary study. The results showed that God's justice, though seemingly unjust, is for Jacob and people today a form of God's participation with all love, which is as complete as possible by including suffering as an integral part of the self. Thus, God's wisdom as an emanation of love for every people and creation is a space of reality for people who are far from justice, prosperity, well-being, health and peace.